2010
DOI: 10.1172/jci39837
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2-Akt1 crosstalk regulates arteriogenesis in mice and zebrafish

Abstract: Arterial morphogenesis is an important and poorly understood process. In particular, the signaling events controlling arterial formation have not been established. We evaluated whether alterations in the balance between ERK1/2 and PI3K signaling pathways could stimulate arterial formation in the setting of defective arterial morphogenesis in mice and zebrafish. Increased ERK1/2 activity in mouse ECs with reduced VEGF responsiveness was achieved in vitro and in vivo by downregulating PI3K activity, suppressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
162
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 143 publications
(170 citation statements)
references
References 49 publications
8
162
0
Order By: Relevance
“…Until recently, no interactions between these two signaling cascades have been appreciated. We have previously demonstrated that under normal conditions in the adult vasculature, AKT inhibits ERK signaling via phosphorylation of RAF1, and that inhibition of PI3K leads to ERK activation (9). The importance of PI3K/ERK interaction is further suggested by studies demonstrating that mice lacking the of RAF1 S259A causes a lymphatic phenotype similar to that observed in Noonan and LEOPARD syndrome patients.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Until recently, no interactions between these two signaling cascades have been appreciated. We have previously demonstrated that under normal conditions in the adult vasculature, AKT inhibits ERK signaling via phosphorylation of RAF1, and that inhibition of PI3K leads to ERK activation (9). The importance of PI3K/ERK interaction is further suggested by studies demonstrating that mice lacking the of RAF1 S259A causes a lymphatic phenotype similar to that observed in Noonan and LEOPARD syndrome patients.…”
Section: Discussionmentioning
confidence: 87%
“…Primary mouse ECs were isolated from mouse embryos or lungs using a protocol similar to that previously described (9). Briefly, embryos or lungs were harvested, minced finely with scissors, and then digested in 25 ml collagenase 0.2% (w/v) at 37°C for 20 minutes (embryo) or 45 minutes (lung).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the involvement of Erk1/2 in regulation of VEGFR2 expression, we used Ad vectors encoding Erk2 fused to the low-activity form of its upstream regulator, Mek1. Whereas the Mek1-Erk2 (ME) hybrid protein is retained in the cytoplasm because of the presence of a nuclear export sequence, mutation of the 4 leucines in the export sequence to alanines (Mek1-Erk2-LA [ME-LA]) dramatically increases its catalytic activity with concomitant nuclear translocation (11,12). Transduction of Ad-ME-LA, but not Ad-GFP or Ad-ME, into FGFR1DN-expressing BAECs restored Vegfr2 mRNA and protein expression to control levels (Figure 1, F and G), which indicates that regulation of VEGFR2 expression by FGF is mediated through an Erk1/2-dependent signaling mechanism.…”
Section: Fgf-induced Erk1/2 Activation Mediates Vegfr2 Expressionmentioning
confidence: 99%
“…In another study, anthrax toxin, whose targets include MEK1/2 [22], appeared to reduce vessel lumen size in zebrafish [23]. During earlier developmental stages, MEK1/2 is also involved in artery specification in both zebrafish and mice [24,25]. Together these findings imply that MEK1/2 may cooperate with VEGFR to regulate blood vessel lumen diameter.…”
Section: Combined Action Of Vegfr and Map Kinase Pathways Maintains Vmentioning
confidence: 93%